2006
DOI: 10.1111/j.1365-2036.2006.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of plasma ghrelin in peptic ulcer disease

Abstract: SUMMARY BackgroundGhrelin is a novel appetite-promoting peptide secreted primarily from the A-like cells in the gastric fundic mucosa. As gastric inflammation caused by Helicobacter pylori infection extends, the number of ghrelinproducing A-like cells is diminished and gastric ghrelin content decreases significantly. We previously reported that plasma levels of ghrelin, which correlated well with the serum levels of pepsinogen (PG) I and PG I/II ratio, decreased as gastric mucosal atrophy increased in non-ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…In contrast to our findings, Suzuki et al (2006) reported that plasma ghrelin levels were significantly higher in patients with peptic ulcer than in those with gastritis without ulcer, which suggests a possible relationship between mucosal injury susceptibility and the elevated plasma ghrelin.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Suzuki et al (2006) reported that plasma ghrelin levels were significantly higher in patients with peptic ulcer than in those with gastritis without ulcer, which suggests a possible relationship between mucosal injury susceptibility and the elevated plasma ghrelin.…”
Section: Discussioncontrasting
confidence: 99%
“…These functions are mediated, at least in part, via vagal nerve pathways 29,30. In gastroduodenal mucosal injury, the levels of plasma ghrelin increased in response to the physiological demand for the purpose of gastroduodenal cytoprotection 31,32. However, in the presence of H. pylori -induced severe gastric mucosal atrophy, the plasma ghrelin concentrations shifted to lower levels 33-36.…”
Section: Pathophysiological Link Between Helicobacter Pylori Infectiomentioning
confidence: 99%
“…[7] Ghrelin regulates appetite, glucose metabolism, adipogenic effects, and energy balance. [19,20] The plasma ghrelin level is elevated in patients with peptic ulcer, [21] including both acylated ghrelin and unacylated ghrelin. [7] Both vagal stimulation and fat ingestion may influence the release of ghrelin through vagus nerve.…”
Section: Discussionmentioning
confidence: 99%